Neurobiological and Hormonal Mechanisms Regulating Women’s Sleep - Dorsey, Alanna; de Lecea, Luis; Jennings, Kimberly J. (Frontiers in Neuroscience, 2021)
Sleep is crucial for optimal well-being and sex differences in sleep quality have significant implications for women’s health. We review the current literature on sex differences in sleep, such as differences in objective and subjective sleep measures and their relationship with aging. We then discuss the convincing evidence for the role of ovarian hormones in regulating female sleep, and survey how these hormones act on a multitude of brain regions and neurochemicals to impact sleep. Lastly, we identify several important areas in need of future research to narrow the knowledge gap and improve the health of women and other understudied populations.